Sosialisasi Pengenalan Zakat Fitrah Terhadap Santriwati Pondok Pesantren Madinatul Quran Desa Betung Ogan Ilir - Saprida Saprida (AKM, 2021)
This community service activity discusses the introduction of zakat fitrah both from the understanding of zakat fitrah, the mandatory requirements for zakat fitrah, the time to pay zakat fitrah, mustahiq zakat, types of objects issued for zakat fitrah and the wisdom of zakat fitrah. The purpose of this community service activity is to provide an introduction to zakat fitrah for students of the Madinatul Quran Islamic Boarding School in Betung Ogan Ilir Village with the hope that the socialization participants can understand the obligation of zakat fitrah for all Muslims who have excess assets. Socialization participants can also find out that zakat can bring closer relationships of affection and love between poor and rich people. Zakat can also cleanse oneself from stingy and despicable morals, and educate oneself to be noble and generous by making it a habit to pay mandates to people who are entitled to receive it.